Development of Tembang Macapat Booklet for Javanese Language Learning in Grade 5th Elementary Schools - Ara, Sekar Dewi Nawang; Rini, Titis Angga; Arafik, Muh. (Angstrom Centre of Education, 2025)
In learning elementary Javanese language, of course, there are still many students who less understanding about the material in it. Moreover, the lack of interesting media and teaching materials can reduce students' interest in learning Javanese language subjects. So, it is necessary to have an alternative to fulfill needs such as the development of teaching materials used by teachers and students, especially in the material of tembang macapat whose contents are more complete, more practical and equipped with pictures that support the material, are colorful and hopefully will attract students' interest. One of the suitable teaching materials developed is 'booklet'. The goal is to produce a valid and practical booklet. The type of research used is development research with ADDIE model which is composed of 5 stages namely analyze, development, design, implementation, and evaluation. The data from the validation results of the macapat song booklet reached very valid criteria with an average of 96.16% and the results of the practicality test of teachers and students reached an average of 95.71% with very practical criteria. After testing the tembang macapat booklet on students, a positive response was obtained, namely learning is more fun, interesting, and easy to use in understanding the material. So it can be concluded that the booklet of tembang macapat for learning Javanese class V is very valid and very practical so it is feasible to use in learning activities.